以下哪个是正确的变量名? A: 3xy B: str C: a3+5 D: (xy)
以下哪个是正确的变量名? A: 3xy B: str C: a3+5 D: (xy)
方程\( xy'' - 5y' + 3xy = {\cos ^2}x \)的通解中包含 (写数字)个独立的任意常量。______
方程\( xy'' - 5y' + 3xy = {\cos ^2}x \)的通解中包含 (写数字)个独立的任意常量。______
计算:2x2•3xy=______.
计算:2x2•3xy=______.
分解因式()x()3()y()-()2()x()2()y()2()+()xy()3()正确的是A.()xy()(()x()+()y())()2()B.()xy()(()x()2()﹣()2()xy()+()y()2())()C.()xy()(()x()2()+2()xy()﹣()y()2())()D.()xy()(()x()﹣()y())()2
分解因式()x()3()y()-()2()x()2()y()2()+()xy()3()正确的是A.()xy()(()x()+()y())()2()B.()xy()(()x()2()﹣()2()xy()+()y()2())()C.()xy()(()x()2()+2()xy()﹣()y()2())()D.()xy()(()x()﹣()y())()2
计算(xy的2次方+3)(xy的2次方)-2x(-x+y)
计算(xy的2次方+3)(xy的2次方)-2x(-x+y)
设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial y}}=\)( )。 A: \({e^{xy}}({x}y^2 + {x^3} + 2y)\) B: \({e^{xy}}({x^2}y + {x^3} + 2y)\) C: \({e^{xy}}({x}y^2 + {x^3} + 2x)\) D: \({e^{xy}}({x}y+ {x^3} + 2y)\)
设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial y}}=\)( )。 A: \({e^{xy}}({x}y^2 + {x^3} + 2y)\) B: \({e^{xy}}({x^2}y + {x^3} + 2y)\) C: \({e^{xy}}({x}y^2 + {x^3} + 2x)\) D: \({e^{xy}}({x}y+ {x^3} + 2y)\)
设\(z = u{e^v}\),\(u = x + y\),\(v = xy\),则\( { { \partial z} \over {\partial x}}=\) A: \({e^{xy}}(1 + xy + {y^2})\) B: \({e^{xy}}(1 + xy + {y^3})\) C: \({e^{xy}}(x+ xy + {y^2})\) D: \({e^{xy}}(y+ xy + {y^2})\)
设\(z = u{e^v}\),\(u = x + y\),\(v = xy\),则\( { { \partial z} \over {\partial x}}=\) A: \({e^{xy}}(1 + xy + {y^2})\) B: \({e^{xy}}(1 + xy + {y^3})\) C: \({e^{xy}}(x+ xy + {y^2})\) D: \({e^{xy}}(y+ xy + {y^2})\)
5、3xy和3xyz是同类项( )
5、3xy和3xyz是同类项( )
已知x+y=3,xy=12,求
已知x+y=3,xy=12,求
下列计算正确的是()。 A: 6x<sup>2</sup>·3xy=9x<sup>3</sup>y B: (2ab<sup>2</sup>)·(-3ab)=-a<sup>2</sup>b<sup>3</sup> C: (mn)<sup>2</sup>·(-m<sup>2</sup>n)=-m<sup>3</sup>n<sup>3</sup> D: (-3x<sup>2</sup>y)·(-3xy)=9x<sup>3</sup>y<sup>2</sup>
下列计算正确的是()。 A: 6x<sup>2</sup>·3xy=9x<sup>3</sup>y B: (2ab<sup>2</sup>)·(-3ab)=-a<sup>2</sup>b<sup>3</sup> C: (mn)<sup>2</sup>·(-m<sup>2</sup>n)=-m<sup>3</sup>n<sup>3</sup> D: (-3x<sup>2</sup>y)·(-3xy)=9x<sup>3</sup>y<sup>2</sup>